High Expression of miR-483-5p Predicts Chemotherapy Resistance in Epithelial Ovarian Cancer - Rattanapan, Yanisa; Korkiatsakul, Veerawat; Kongruang, Adcharee; Siriboonpiputtana, Teerapong; Rerkamnuaychoke, Budsaba; Chareonsirisuthigul, Takol (MicroRNA, 2021)
Background: Ovarian cancer is the most deadly cancer that requires novel diagnostics and therapeutics. MicroRNAs are viewed as essential gene regulatory elements involved in different pathobiological mechanisms of many cancers, including ovarian cancer. Objective: This study examined the relationship between microRNA (miRNA) expression and response to platinum-based chemotherapy. Methods: Genome-wide miRNA expression analysis was conducted using Epithelial Ovarian Cancer (EOC) tissues from 25 patients with 17 malignant tumors and eight benign ovarian tumors. Candidate miRNAs that respond to platinum-based chemotherapy were selected for validation by quantitative RT-PCR. Results: Among 2,578 mature human miRNAs, high expression of miR-483-5p correlated with poor responses to platinum-based chemotherapy in EOC patients. Furthermore, high levels of miR-483-5p in the resistant group suppressed expression of the apoptotic regulator TAOK-1. Conclusion: A possible marker for the prediction of chemotherapy response and resistance in patients may be miR-483-5p. Choosing the right treatment for each patient with EOC can avoid the risk of developing chemotherapy resistance.
Keywords: miR-483-5p